S-adenosylmethionine treatment diminishes the proliferation of castration-resistant prostate cancer cells by modulating the expression of miRNAs - Schmidt, Thomas (Archivum immunologiae et therapiae experimentalis, 2024)
AdoMet (S-adenosylmethionine) inhibits cancer cell proliferation and migration via epigenetic alterations. This study aimed to investigate whether AdoMet may cause alterations in microRNA (miRNA) expression profiles that are important for the initiation and progression of prostate cancer. PC-3 cells were treated with AdoMet before miRNA sequencing. A total of 17 differentially expressed miRNAs were detected. Target gene prediction was performed by means of databases. Results were aligned to transcriptomic data. The bioinformatic analysis revealed upregulation of anticancerogenic genes, downregulation of cancerogenic-related processes and pathways. Knocking down hsa-miR-192-5p in PC-3 cells resulted in downregulation of cancer cell proliferation, thus confirming these results.
Gesehen am 07.04.2025